O Imaginário sobre robôs em séries de ficção científica : a saga Battlestar Galactica (1978 – 2010) - Lívia de Pádua Nóbrega (2020)
The presente research aimed to map the senses constructed and put into circulation through narratives about robots in Science Fiction series over the time (1978 – 2010). The proposed time frame refers to what was taken as an empirical object: the American saga Battlestar Galactica due to the consideration of its character of exemplarity in relation to the dialogue with the context of its time, to the forms of construction and understanding narratives triggered in the format of seriality and the themes of techno-science mobilized. Observing that the robots stories have the ability to activate the collective imaginary about human condition and offer symbolic compensation for the drives formed by social constraints, is analyzed how the mythology built by the production provides the need to symbolize of human desires and fears. Thus, they articulate creators and audiences through media productions. To this end, the perspective Theory of the Imaginary, by Gilbert Durand and his methodological procedures of Mythocritics and Mythanalysis were adopted. During this course, it was noticed the appropriation of the Golem myth in fiction about artificial beings, its stereotype process with the popularization of the robot figure and a principle of transformation and saturation of its metallized figurations to make room for more appropriate representations of new life forms and subjectivity. The main results account for Science Fiction as a style of multiple and even disparate matrices, which each production appropriates in its own way in order to confer particular tones; The “robot” theme emerges from the tension between simple elements familiar to the audience – such as religiosity and mysticism – and relatively new and complex elements – such as artificial consciousness – in order to alleviate the cognitive estrangement that technoscientific questions can generate; the idea that Science Fiction develops a thematic complexity whose approach is benefited under the serial dynamics - what makes sci-fi series the ideal universe for dealing with such issues, developed gradually; superficial adherence, but which becomes more complex over time, to the technoscience ideation system and Science Fiction as an important place to deal with contemporary science and technology issues, through a way of legitimate knowledge in its creative specificities.